2012
DOI: 10.1111/acps.12029
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy improves mental and physical health in schizophrenia: a randomised controlled trial

Abstract: Exercise therapy, when performed once to twice a week, improved mental health and cardiovascular fitness and reduced need of care in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
193
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(212 citation statements)
references
References 51 publications
14
193
2
3
Order By: Relevance
“…The observation that antipsychotic medication use was not associated with a lower aerobic fitness is in accordance with previous research (Scheewe et al, 2013). The current data therefore indicates that the exposure to an unhealthy lifestyle rather than to antipsychotic medication use is associated with a worse performance on aerobic exercise tests.…”
Section: Factors Associated With the Astrand-rhyming Test Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…The observation that antipsychotic medication use was not associated with a lower aerobic fitness is in accordance with previous research (Scheewe et al, 2013). The current data therefore indicates that the exposure to an unhealthy lifestyle rather than to antipsychotic medication use is associated with a worse performance on aerobic exercise tests.…”
Section: Factors Associated With the Astrand-rhyming Test Performancesupporting
confidence: 92%
“…Associations between negative symptoms and impaired aerobic fitness have been reported before in this population (Scheewe et al, 2013). However in contrast, Strassnig et al (2011) found that aerobic fitness was only associated with the severity of positive symptoms and not with negative symptoms.…”
Section: Factors Associated With the Astrand-rhyming Test Performancementioning
confidence: 47%
See 1 more Smart Citation
“…2015;37 (4) sets of 10 to 15 maximum repetitions of resistance exercises for six different muscle groups per week. 35 These sessions lasted 1 hour and took place twice a week for 6 months. Their results showed a 20% decrease in PANSS total score and significant decreases in positive, negative, and other PANSS scores as compared with a control group undergoing occupational therapy.…”
Section: Discussionmentioning
confidence: 99%
“…diet, interpersonal encounter, environmental change) factors, which may, when taken together, help to explain the significant placebo rate in antipsychotic drug trials [1]. Exercise is one factor that has been shown to temporarily enhance treatment effects in schizophrenia [2][3][4][5][6][7][8]. Whether side effects are enhanced or dampened after exercise, however, has not been addressed in these studies.…”
mentioning
confidence: 99%